Effects of the thyroid hormone derivatives 3-iodothyronamine and thyronamine on rat liver oxidative capacity - Venditti, P. (Mol Cell Endocrinol, 2011)
Thyronamines T(0)AM and T(1)AM are naturally occurring decarboxylated thyroid hormone derivatives. Their in vivo administration induces effects opposite to those induced by thyroid hormone, including lowering of body temperature. Since the mitochondrial energy-transduction apparatus is known to be a potential target of thyroid hormone and its derivatives, we investigated the in vitro effects of T(0)AM and T(1)AM on the rates of O(2) consumption and H(2)O(2) release by rat liver mitochondria. Hypothyroid animals were used because of the low levels of endogenous thyronamines. We found that both compounds are able to reduce mitochondrial O(2) consumption and increase H(2)O(2) release. The observed changes could be explained by a partial block, operated by thyronamines, at a site located near the site of action of antimycin A. This hypothesis was confirmed by the observation that thyronamines reduced the activity of Complex III where the site of antimycin action is located. Because thyronamines exerted their effects at concentrations comparable to those found in hepatic tissue, it is conceivable that they can affect in vivo mitochondrial O(2) consumption and H(2)O(2) production acting as modulators of thyroid hormone action.